Legal Entities – As Subjects of Civil Law - Nadirbekova Umida Karamatdin qizi; Farhad Kutlimuratov Kalbaevich; Farhad Kutlimuratov Kalbaevich (Periodica Journal, 2022)
In this article, the importance and role of obligations of legal entities in the structure of legal relations is reflected on the basis of normative legal documents and legal literature
Keywords: entities; legal capacity; civil-legal relations; Legal